Effect of Noni Fruit Flour (Morinda citrifolia L.) in ration on the percentage of boneless meat of KUB chickens (Ayam Unggul Balitnak). - Sofiyudin; Jatmiko; Dewi Wahyuni (Universitas Djuanda, 2026)
Noni fruit or noni fruit can be used as a natural feed additive in livestock rations and contains many antibacterial substances such as xeronine, proxeronine, serotonin, daì mmaì caì nthaìl This study aims to test the effect of the use of noni fruit flour (Norinda citrifolia L.) in rations on the percentage of boneless KUB chickens (Kampung Unggul Balitnak). The research was carried out from July 1 to August 7, 2024 in Padasuka Village, Ciomas District, Bogor Regency. This study used 100 KUB chickens (unisex). This study used a complete randomized design (RAL) with 5 treatments and 4 replicates. The data was analyzed using variety analysis (ANOVA) and Ducan's follow-up test. R0 = control ration, R1 = addition of 0.75% noni fruit flour to the ration, R2 = addition of 1% noni fruit flour to the ration, R3 addition of noni fruit flour 1.25% to the ration, R4 = addition of 1.50% noni fruit flour to the ration. The variables observed in this study were the percentage of chest and thighs, the percentage of boneless breasts and thighs, the percentage of skin on the chest and thighs, the ratio of breasts and thighs, and the ratio of bones to breast and thigh flesh. The results of this study are that the administration of noni fruit flour at the level of 0.75% to 1.50% has not shown a real effect (P>0.05) on the percentage of breast and thigh, the percentage of boneless chest and thighs, the percentage of skin on the chest and thighs, the percentage of bones and thighs, and the ratio of bones to breast and thigh meat in KUB chickens (Kampung Unggul Balitnak). The conclusion of this study is that the administration of noni fruit flour at the level of 0.75% to 1.50% could not increase the percentage of bonelessness in the breast and thighs of KUB chickens